2019
DOI: 10.1063/1.5087437
|View full text |Cite
|
Sign up to set email alerts
|

Magnetized plasma sheath properties in the presence of Maxwellian low-temperature and non-Maxwellian high-temperature electrons

Abstract: The characteristics of a magnetized plasma sheath in the presence of two-groups of electrons, namely, low-temperature electrons (LTEs) and high-temperature electrons (HTEs), have been studied using the fluid model. The LTEs are considered to obey the Boltzmann distribution, whereas the HTEs follow the so-called q-nonextensive distribution. The Bohm-sheath criterion which gets modified is developed for such plasmas, and the compiled fluid equations are solved numerically. The obtained results signify that the q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…In the above boundary conditions, the electrostatic potential at the presheath-sheath interface region is considered to be zero; however, a small electric field is assumed to prevent a divergence of the numerical results. Moreover, this ensures that the plasma approximation holds and the result is case insensitive [40]. A comparative study of plasma-sheath parameters using kinetic and fluid models at constant d d = = 0.12 ps n ps and β ps = 4.5 is depicted in figures 14-16.…”
Section: Resultsmentioning
confidence: 99%
“…In the above boundary conditions, the electrostatic potential at the presheath-sheath interface region is considered to be zero; however, a small electric field is assumed to prevent a divergence of the numerical results. Moreover, this ensures that the plasma approximation holds and the result is case insensitive [40]. A comparative study of plasma-sheath parameters using kinetic and fluid models at constant d d = = 0.12 ps n ps and β ps = 4.5 is depicted in figures 14-16.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, the non-extensive distribution of electrons has been applied to study the fundamental problems of plasma sheath under different physical conditions [19][20][21][22][23][24][25][26][27][28][29][30]. Dhawan et al [21] considered the non-extensive distribution of electron, ion temperature and ion neutral collision in the simulation.…”
Section: Introductionmentioning
confidence: 99%
“…They have found that the q value can affect the width of plasma sheath. Basnet et al [25] studied the characteristics of the magnetized plasma sheath in the presence of both Boltzmann and non-extensive distribution electrons using the fluid model. The results have shown that the parameter q and density ratio have significant effects on the parameters of the magnetized plasma sheath.…”
Section: Introductionmentioning
confidence: 99%
“…Such a thin layer is termed as sheath that plays a momentous role in analyzing the plasma-surface interactions [8]. The investigation of sheath characteristics in different plasma systems has been carried out by several researchers [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. The sheath characteristics have been found to show a distinct nature, when negative ions are introduced in the system [23,[29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…The examination of two non-Maxwellian electrons in unmagnetized electropositive plasma has been carried by Hatami and Tribeche [12]. Basnet and Khanal [11] have analyzed the Maxwellian and non-Maxwellian electrons in magnetized electropositive plasma. The impact of ionization on sheath characteristics with two-temperature non-extensive distributed electrons has been investigated by Dhawan et al [21].…”
Section: Introductionmentioning
confidence: 99%